THU0549 Systemic treatment for acute anterior uveitis (synthetic and biologic disease-modifying antirheumatic drugs): a systematic review. (15th June 2017) - Gόmez-Gόmez, A; Loza, E; Rosario, MP; Carmona, L; Espinosa, G; Morales, JM García Ruíz de; Herrera, JM; Muñoz-Fernández, S; Cordero, M
Abstract : Background: Acute anterior uveitis (AAU) is the most common form of uveitis. Most of them are idiopathic, followed by those related to rheumatic conditions. One third of AAU patients may present recurrences, some requiring systemic disease-modifying antirheumatic drugs (DMARDs). The use of DMARDs in AAU is heterogeneous. Objectives: To perform a systematic and critical review of the literature about the use of synthetic and biologic DMARDs in adult patients with AAU. Methods: Selection criteria: Articles including adult patients with non-infectious AU treated with synthetic or biologic DMARDs including efficacy, and/or safety or cost-effectivity data were selected. Only meta-analysis, systematic reviews, clinical trials and observational studies (OS) were included. Search strategies for Medline, Embase and Cochrane Library databases up to 3–2016 were designed. Article selection: 2 independent reviewers. Selected articles were analyzed in detail. Quality asessment of the studies: Oxford scale and Jadad scale were used. Analysis and data presentation: evidence and results tables. Results: 14 articles included, 2 RCTs and 12 OSs, with low or moderate quality. The mean duration/follow-up, number (n) and patients characteristics were highly variable. The definition of the anatomic classification of AUs was generally not clear. Systemic DMARDs were used, including Methotrexate (MTX), Azathioprine (AZA), Cyclosporine A (CsA) and anti-TNFα (Adalimumab (ADA), Golimumab (GLM)), at usual dosage prescription. Number of flares, disease activity and corticoid sparing (CS) effect were the most common outcomes, with big differences between studies in variables included and their definitions. MTX showed efficacy in disease remission, n of flares, time between flares, lower activity and CS effect. SSZ showed lower n of flares and improvement in visual acuity (VA) in AS-associated AAU patients. AZA (low quality RCT) showed no differences in VA, Tyndall, flares or IOP. A prospective OS showed lower activity and CS effect. CsA (moderate quality OS) showed efficacy improving activity and as CS agent (mid/long term). Anti-TNFα: ADA, (2 OSs) with SpA-associated AU patients lowered n of flares (mid/long term), can improve VA, Tyndall and be used as CS agent. GLM in AU patients refractory to DMARDs (some to other biologics), showed CS effect in 2 studies. One showed improvement in VA and Tyndall, but not in OCT or n of flares. Adverse events recorded were those usually registered for all these drugs. Conclusions: Evidence quality is low. Great variability. MTX showed efficacy in idiopathic and systemic disease-associated (SDA) AU.(EL 2c; RG B). SSZ showed efficacy in idiopathic and SDA AU.(EL 3a; RG B-C). AZA seems to be effective in naïve and DMARDs-refractory AU (EL 3a; RG C). CsA showed efficacy in idiopathic and SDA AU (EL 2c; RG B-C). ADA showed efficacy in idiopathic and SDA AU, naïve or DMARDs-refractory AU (EL 2c; RG B). GLM showed efficacy in DMARD-refractory AU (2nd line and further) and other biologic therapies (EL 3a; RG B-C). Disclosure of Interest: None declared